Diastereoselective Synthesis of Methanopyridoxazocinones - Detistov, Oleksandr S.; Panda, Siva S.; Steel, Peter J.; Asiri, Abdullah M.; Hall, C. Dennis; Katritzky, Alan R. (Synlett, 2014)
Two approaches to the synthesis of oxygen-bridged tetrahydropyridones have been developed. In the first approach, substituted pyrido[4,3-g][1,3]oxazocines derivatives were prepared by diastereoselective one-pot reactions of substituted 7-azacoumarins with enolizable ketones and non-bulky primary amines. In the second one, 3-amido-7-azacoumarins were reacted with enolizable ketones in the presence of a base to form diastereomerically pure pyrido[4,3-g][1,3]oxazocines.
Keywords: azacoumarin; diastereomer; chirality; bridged heterocycles; synthesis